ANALISIS YURIDIS PERLINDUNGAN KONSUMEN TERHADAP PRAKTIK PINJAMAN ONLINE ILEGAL DI INDONESIA - Naek Efendi; Hasnah Aziz; Asep Mulyana; Tugimin Harjotaruno; Dadang Rachmat; Juhana Nuryana (Berajah Journal, 2026)
Abstract The development of financial technology (fintech) lending in Indonesia has brought significant transformation in financial service access, yet simultaneously raised serious problems regarding the proliferation of illegal online lending practices. These practices involve misuse of consumers personal data, digital intimidation, exorbitant interest rates, and various actions that substantially harm consumers. This article aims to analyze juridically the legal protection framework for consumers against illegal online lending practices in Indonesia. The research method used is qualitative with a normative-empirical legal approach. Data was collected through studies of legislation, court decisions, Financial Services Authority reports, and scientific literature studies. The results show that consumer protection against illegal online lending practices faces multidimensional challenges, including regulatory weaknesses that do not comprehensively regulate digital lending aspects, law enforcement limitations due to the transnational nature of perpetrators, and low consumer financial literacy. This article recommends the need for harmonization of legislation, strengthening of cross-institutional cooperation, and revitalization of consumer education to create an online lending ecosystem that effectively protects consumer rights.